Stone age landscape use in the Olifants River Valley, Western Cape - Hallinan, Emily Sarah (Department of Archaeology, 2014)
This thesis investigates changing patterns of landscape use throughout the Earlier (ESA), Middle (MSA) and Later Stone Ages (LSA) in the Olifants River Valley in the Western Cape, South Africa. Stone Age surface assemblages are all too often neglected in favour of stratified, datable cave sequences, overlooking important insights into changing behavioural patterns at a broader scale. The Olifants River Valley offers the opportunity for integrating a rich surface lithic record with excavated rock shelter occupation dating from the LSA and extending back into the early part of the MSA. This thesis approaches Stone Age landscape use with reference to a hypothesis proposed by Hilary Deacon, framing the MSA within the context of earlier and later patterns of behaviour. Based on observations from sites across South Africa, Deacon described ESA landscape use as stenotopic, occupying a narrow ecological niche focused on permanent water sources, and LSA landscape use as eurytopic, making use of a much broader range of habitats but with a specific focus on rock shelters as domestic sites. Deacon suggested that the intervening MSA, in its later stages, shows a pattern that anticipated LSA landscape use, with an increasing emphasis on caves and a wider-ranging exploitation of resources across different environmental zones. Surface surveys were carried out in the Olifants River Valley, mapping temporally diagnostic artefacts and their association with different topographic features. In this thesis, I test Deacon's model and show that it can be applied to the study area, observing distinctive preferences for certain sites and raw materials, and approaching changes in patterns of artefact discard from a technological perspective.